Triclosan-induced liver and brain injury in zebrafish (Danio rerio) via abnormal expression of miR-125 regulated by PKCα/Nrf2/p53 signaling pathways. (February 2020) - Wang, Caihong; Huang, Wenhao; Lin, Jiebo; Fang, Fang; Wang, Xuedong; Wang, Huili
Abstract: Triclosan (TCS) is widely used in personal care products, and its chronic exposure leads to severely toxic effects in zebrafish ( Danio rerio ). PKCα, Nrf2 and p53 are three important signaling pathways concerned with cell development. Herein, we speculated on and verified a novel TCS regulatory pathway: (1) TCS acted on GPER (G-protein-coupled estrogen receptor) to activate MAPK/ERK pathway, further resulting in the expression changes of protein kinase C (PKC) family; (2) PKC participated in Nrf2 phosphorylation; (3) The expression of miR-125b was regulated by Nrf2; and (4) The expression changes of related genes in the PKCs-Nrf2-ARE pathway showed the specificity of zebrafish tissue and organ. TCS exposure led to down-regulation of the Nrf2 and phosphorylated Nrf2(Ser40) protein in diencephalon nucleus, stratum marginale and stratum centrale areas in adult zebrafish brain. The phosphorylated Nrf2(Ser40) was mainly expressed in PGz area, while it was not the case for Nrf2. Both Nrf2 and phosphorylated Nrf2 were activated by TCS exposure; however, the changing trend of PKCs was opposite to that of Nrf2 in the liver. Both DAPI staining and Merge images demonstrated that TCS induced oxidative phosphorylation, and phosphorylated Nrf2 is translocated into the nucleus as the transcription factor to regulate gene transcription in liver and brain. Nrf2 over-expression increased accumulation of lipid droplets in yolk, brain and liver, resulting from the upregulation of pri-miR-125b1, pri-miR-125b3, but not pri-miR-125b2. These findings reveal the upstream regulation mechanism of miR-125b for TCS-induced fat-metabolism disorder from the regulatory perspective of the pri-miR-125b promoter region. Highlights: TCS acts on GPER (Gp-protein-coupled estrogen receptor) to activate MAPK/ERK pathway. Activation of MAPK/ERK induces Ca 2+ excessive release from endoplasmic reticulum to active PKCα. PKCα takes part in Nrf2 phosphorylation, which is translocated into nucleus and bound to the promoter region of pri-miR-125b. Abnormal expression of miR-125b regulatory target genes is related to fat-metabolism disorder and apoptosis. The upstream regulatory mechanism of miR-125b for TCS-induced fat-metabolism disorder.